Treatment nonadherence factors among rural South African patients with diabetes mellitus attending primary care facilities - Mabunda, Milliscent; Mokgatle, Mathildah; Hoque, Muhammad (Orapuh Journal, 2024)
Introduction Diabetes mellitus (DM) is a significant global public health challenge, with effective management relying heavily on patient adherence to treatment protocols. In South Africa, particularly in low-resource settings like the Soweto area in the Johannesburg Health District, treatment nonadherence among diabetic patients is a pressing concern, contributing to poor health outcomes and increased healthcare costs. Purpose This study aimed to identify and analyze factors associated with treatment nonadherence among patients diagnosed with diabetes mellitus attending primary healthcare facilities in Soweto, Johannesburg Health District, South Africa. Methods This was a cross-sectional quantitative study conducted among 490 diabetic patients attending primary healthcare facilities in Soweto using structured anonymous questionnaires. The chi-squared test was used to assess associations between treatment nonadherence and various factors. SPSS version 27 was used to analyze the data. Results The average age of the patients was 59 years, and 66% were female. The nonadherence rate among the patients was 31%, with 80% having occasionally missed a dose of their medication. Gender, marital status, monthly household income, number of years living with diabetes, and adherence to diet were significantly associated with nonadherence to diabetes treatment (p < 0.05). Conclusion The study highlights the multifaceted nature of treatment nonadherence among diabetic patients in Soweto. Addressing these factors requires a comprehensive approach, including improving patient education, enhancing social support, and addressing socioeconomic barriers.